2021
DOI: 10.55563/clinexprheumatol/4c36nr
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic features of lymphoma of the major salivary glands diagnosed with ultrasound-guided core needle biopsy in Sjögren's syndrome

Abstract: Objective. To identify ultrasound (US) features of lymphomas (L) of major salivary glands (SGs) in primary Sjögren's syndrome (pSS) patients and to differentiate US pattern of L and non-L. Methods. Prospectively, from September 2019 to March 2021, 27 pSS-patients with clinical findings suspicious for L of the SGs underwent US evaluation followed by US-guided core-needle biopsy (CNB). For each patient, we assessed the OMERACT score, dichotomised (0/1 "lower", 2/3 "higher"), and we compared it between L-pSS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“… 66 In pSS patients with inhomogeneous glandular patterns, especially those with higher OMERACT scores (2 and 3), the presence of a newly diagnosed focal lesion is suggestive of lymphoma. 33 However, in this clinical scenario, other focal benign and malignant lesions typically found in the general population must first be ruled out ( Figure 4 ). 67 , 68 In the general population, focal lesions in SGs are rare.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“… 66 In pSS patients with inhomogeneous glandular patterns, especially those with higher OMERACT scores (2 and 3), the presence of a newly diagnosed focal lesion is suggestive of lymphoma. 33 However, in this clinical scenario, other focal benign and malignant lesions typically found in the general population must first be ruled out ( Figure 4 ). 67 , 68 In the general population, focal lesions in SGs are rare.…”
Section: Differential Diagnosismentioning
confidence: 99%
“… 29 , 33 However, recent studies highlighted that NHL of major SGs can also present as well-defined focal abnormalities in SGs with no diffuse background lymphomatous infiltration. 19 , 33 It has been hypothesized that such areas may represent foci of actively expanding B-cell clones, 33 in keeping with the currently accepted model of lymphomagenesis in pSS. 66 Research has also demonstrated that focal NHL exhibits recurrent, distinctive sonographic features and tends to present as a very hypoechoic, oval, well-defined, homogenous lesion, with posterior acoustic enhancement, which frequently contains thin, hyperechoic septa and signs of hypervascularity on SGUS and color Doppler imaging.…”
Section: Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…The SG ultrasonographic pattern might represent another predictor, due to the proven association with clinical, serological and histological features of lymphoproliferative risk and its ability to define the ESSDAI glandular domain in pSS, 21 , 108 , 124 , 126 , 185 as recently reported by Lorenzon et al 186 …”
Section: Lymphoma In Pssmentioning
confidence: 70%
“…Promising innovations are ultrasound elastography (with algorithms to evaluate quantitatively the tissue stiffness of the salivary gland tissue [ 50 ], the application of artificial intelligence to automatically score for biopsy purposes [ 51 ], and the ultrasound-guided core needle biopsy of major salivary glands which could represent an alternative to surgical biopsy [ 52 ].…”
Section: Role Of New Molecular Image Strategies In Sjogren’s Syndromementioning
confidence: 99%